In vitro and in vivo efficacy of the antimycobacterial molecule SQ109 against the human pathogenic fungus, Cryptococcus neoformans - Alkashef, Nour M.; Salama, Ehab A.; Anandakrishnan, Ramu; Hazbun, Tony R.; Hoernig, Micah V.; Brown, Anne M.; Lawrence, Christopher B.; Seleem, Mohamed N. (PLOS Neglected Tropical Diseases, 2025)
Cryptococcosis is an opportunistic fungal infection affecting individuals with compromised immunity, particularly those with HIV. The limited accessibility to effective treatments and treatment-related toxicities underline the need for more effective therapeutic options. In this study, we conducted a whole-cell screening of 3,700 FDA-approved drugs and clinical molecules against the Cryptococcus neoformans H99 strain. The anti-mycobacterial agent SQ109 was identified as one of the most potent hits, with broad antifungal activity. SQ109 exhibited potent activity against Cryptococcus spp., with an MIC90 of 4 μg/mL. In the time-kill assay, SQ109 demonstrated a fungicidal activity on proliferating cryptococcal cells in a concentration-dependent manner. Unlike fluconazole (FLC) and flucytosine (5-FC), C. neoformans showed a negligible tendency to develop resistance to SQ109 during frequent passaging. Furthermore, SQ109 exhibited a potent efficiency in the murine model of cryptococcal infection, resulting in a 50% survival rate among animals treated with 25 mg/kg for 10 consecutive days. The transcriptomic analysis revealed that SQ109 disrupts ergosterol biosynthesis, affecting membrane integrity and oxidative homeostasis. Additionally, molecular docking and structural analysis indicated that squalene synthase protein ERG9 is the most likely target of SQ109 within the ergosterol biosynthesis machinery of cryptococcal cells. Notably, SQ109 potentiates the activity of the standard antifungal FLC, as well as other ergosterol inhibitors, with a fractional inhibitory concentration Index (ΣFICI) ranging from 0.38 to 1. These findings highlight the therapeutic potential of SQ109 in combating cryptococcal infections, both as a standalone therapy and as an adjuvant to FLC monotherapy.